41 Adapting a 2 day communication skills course for the covid-19 clinical and learning environment. Feedback and evaluations from day 1. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Griffiths, Jo; Gallard, Sian; Rawlinson, Fiona; Stacey, Mark; Hayes, Jo; Harris, Dylan; Grose, James; Richards, Jo
Abstract : Background/Introduction: Social distancing and work load as a result of Covid-19 has resulted in the loss of face to face (F2F) education in health care settings. The need for greater use of telephone and video consultations, in addition to mastering optional communication whilst wearing personal protective equipment (PPE) during the pandemic has created additional challenges and learning needs at a time when palliative care skills are in great need. The Cardiff MSc includes practical communication skills as part of the annual F2F teaching. Content and delivery style needed to change in 2020 to reflect the current situation. Methods: Stakeholder analysis of curriculum content to inform the revised programme and delivery and evaluation of the sessions. Results: Discussion led to the development of a combination of webinars, interactive demonstration using specifically filmed scenarios prompting discussion in small groups, group discussions of challenges and strategies for current communication and role play in small groups of virtual consultations with formative feedback for participants. There was a 45% response rate for immediate evaluation and 32% response rate for the delayed evaluation 4 weeks following the day. Immediate evaluation showed the majority of participants (96%) rated the sessions of the day 'good' or 'very good'. On delayed evaluation, 90% of respondents reported a solid or comprehensive understanding of the concepts, 66% reported already using what they had learnt in practice. Conclusions: The previously F2F communication skills teaching successfully translated to the online environment, including using 'breakout groups' to hold interactive demonstrations as prompts for discussion and to role play virtual and telephone consultations to help participants reflect on and develop optimal communication skills for these situations.